2012
DOI: 10.1136/jramc-158-04-15
|View full text |Cite
|
Sign up to set email alerts
|

Balkans Syndrome: A Potential Link Between Multiple Sclerosis and Hypervaccination

Abstract: Balkans Syndrome is a recent term that has been widely used in the media to describe a heterogenous group of medical conditions that presented in soldiers following deployment on military operations to the former Yugoslavia and its neighbouring countries. These individuals had been subjected to an intense and protracted course of vaccinations (termed hypervaccination) prior to deployment, which has subsequently been implicated by the media as the cause of this disease. We describe the case of a 33-year old arm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This mechanism could bring about the degradation of unsaturated fatty acids with consequent demyelination, as observed in a case of CO-intoxication [27]. In the present case, an NMR was not performed, though it is the test that would have accurately shown the possible demyelination [28]. Moreover, the glycine absorbed by the body, and subjected to oxidative deamination in the liver, had conditioned the hepatic necrosis with hyperammonemia that competed to depress brain activity.…”
Section: Discussionmentioning
confidence: 72%
“…This mechanism could bring about the degradation of unsaturated fatty acids with consequent demyelination, as observed in a case of CO-intoxication [27]. In the present case, an NMR was not performed, though it is the test that would have accurately shown the possible demyelination [28]. Moreover, the glycine absorbed by the body, and subjected to oxidative deamination in the liver, had conditioned the hepatic necrosis with hyperammonemia that competed to depress brain activity.…”
Section: Discussionmentioning
confidence: 72%
“…Recent studies showed peculiar echocardiography parameters changes in elite athletes (Vacchiano and Vyshka, 2012 ; D'Ascenzi et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…An adequate device monitoring, especially for cardiac and other high-risk devices [52][53][54][55][56], based on use of National databases, on specific applications, allowing a quick and effective action in case of malfunctioning, must be considered. A recent analysis about the transcatheter aortic valve implantation (T.A.V.I.)…”
Section: Discussionmentioning
confidence: 99%